1997
DOI: 10.2307/1592347
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Coccidia on 43 Poultry Farms in Argentina

Abstract: Fecal samples from 43 broiler and breeder farms in the Entre Rios and Buenos Aires districts of Argentina were examined for Coccidia. Thirty-eight samples were positive by microscopic examination after salt flotation, with counts of 138 to 415,800 oocysts per gram of feces. Samples were aerated for 2 days and inoculated into 21-day-old chicks for determination of prepatent period. Eimeria praecox was conclusively identified in 56% of the samples by producing typical oocysts (17 x 21 microns) in the feces by 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 14 publications
7
25
0
2
Order By: Relevance
“…In the current study, high prevalence of four important species of Emeria such as E. tenella, E. acervulina, E. necatrix and E. maxima were identified. This finding was in agreement with reports from Iran (Hadipour et al, 2013), Ethiopia (Ashenafi et al, 2004), Jordan (Al-Natour et al, 2002), France (Williams et al, 1996), and Argentina (McDougald et al, 1997) suggesting that those species of Eimeria were widespread in most countries. On the other hand, Hadipour et al (2011) reported that at least four species of Eimeria (E. tenella, E. acervulina, E. necatrix and E. maxima) were found in the litter of flock, while the E. tenella was the most rampant species (24%) followed by E. acervulina (18%), E. necatrix (12%) and E. maxima (10%).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, high prevalence of four important species of Emeria such as E. tenella, E. acervulina, E. necatrix and E. maxima were identified. This finding was in agreement with reports from Iran (Hadipour et al, 2013), Ethiopia (Ashenafi et al, 2004), Jordan (Al-Natour et al, 2002), France (Williams et al, 1996), and Argentina (McDougald et al, 1997) suggesting that those species of Eimeria were widespread in most countries. On the other hand, Hadipour et al (2011) reported that at least four species of Eimeria (E. tenella, E. acervulina, E. necatrix and E. maxima) were found in the litter of flock, while the E. tenella was the most rampant species (24%) followed by E. acervulina (18%), E. necatrix (12%) and E. maxima (10%).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previously reported by except that E. necatrix was not detected [9]. These results suggesting that those species of Eimeria are widespread in most countries where poultry are produced on a commercial basis [15,16,17,18].The overall prevalence of Eimeria spp. among broiler chickens in Khartoum State was 5.5%, this rate is low compared with previous studies in other countries, in Ethiopia 20.6 %, in Egypt 21.24 %, in Zaria, Nigeria 33.3% and 37.1 %, 78 % in Jordan, 55.9 % in Iran, 71.9 % in Pakistan , 88.4 % in Argentina and 92 % in Romania [15,16,19,20,21,22,23,24].…”
Section: Discussionsupporting
confidence: 93%
“…We found high prevalences of four important species of coccidia: E. tenella, E. acervulina, E. necatrix and E. maxima. These results are in agreement with reports from Ethiopia (Ashenafi et al, 2004), Jordan (Al-Natour et al, 2002), France (Williams et al, 1996), and Argentina (McDougald et al, 1997) suggesting that those species of Eimeria are widespread in most countries. The high prevalence of the infection in studied native chicken farms in the current study, indicates the maintenance of oocysts in the farm environment, improper cleaning and disinfections methods in the native chicken houses and indiscriminate scavenging behaviour.…”
Section: Discussionsupporting
confidence: 92%